The Effect of Automated Teller Machines (ATM) on Customer Satisfaction at Bank Syariah Indonesia Duri Branch Office - Melisa Sinta Sari (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2022)
This study aims to determine the effect of Automated Teller Machines (ATM) on Customer Satisfaction at Bank Syariah Indonesia Duri Branch Office. This study uses a quantitative approach. The population in this study were all customers of Bank Syariah Indonesia (BSI) Duri Branch Office. The data collection technique used multiple linear regression data analysis tools. Data collection techniques were carried out by distributing questionnaires to 100 customers who had been tested for validity and reliability. The data analysis technique used to answer this research hypothesis is multiple linear regression analysis with the help of software SPSS versi 16.0. The results of this study indicate that the Automated Teller Machine Service (ATM) variable has a significant effect on customer satisfaction. This is evident from the results f-count 88,723 f-table = 2,31 with significance level 0,000 0,05 Partially, the assurance and empathy variables have a significant effect on satisfaction, with the t-count t-table, but the physical evidence, reliability and responsiveness variables have no significant effect on satisfaction with the t-count t-table. The coefficient of determination (R-Square shows the number 0.825%. This is the dependent variable (customer satisfaction) influenced by the independent variable (ATM services) of 82.5% and 17.5% (100%-82.5%) influenced by other variables that were not included in this study.